[Tobacco Institute Report on Cessation Legislation] - BILL KLOEPFER (Tufts Archival Research Center, 2007)
Marginalia; Missing Page(s); Memo from Bill Kloepfer to Samuel D Chilcote, Jr regarding cessation legislation. Introduces missing summary of cessation praogram bills according to intended beneficiaries. Covers the general public, Medicare beneficiaries, youth, federal employees, women, Native Americans, and the military.